Analisis Pengaruh Faktor-Faktor Teknologi Informasi Terhadap Kinerja Pegawai: Pada Dinas Pengelolaan Teknologi Informasi dan Komunikasi Provinsi Papua - Soelaiman, Irma Riyani; Kambuaya, Balthasar; Wambrauw, Oscar O. (Magister Manajemen Universitas Cenderawasih, 2023)
The aim of this research are to examine and determine the factors of Information, Computer Network and Human Resource that influence the performance from Department of Information and Communication Technology Management Papua in simultaneously and partial and be known between those factor whose more in dominant towards it. The method used in this research is descriptive quantitative, with sample taking around 46 respondents. This research was using SPSS Verse 16.00 to see the issues arise and examine the truth of hypothesis from this research by using Testing data collection tool (test validity and reliability testing), Testing Linear Regression Model Analysis Tool (Test of linearity, Multikoilnearitas Test, Test heteroscedasticity, normality test), Data Analysis (Frequency Distribution Analysis, Multiple Regression Analysis, Hypothesis Testing F for the First and Second t-test for the hypothesis). The result of this research shown that simultaneous, information, Computer Networks and Human Resources have a significant effect on employee performance management of the Office of Information Technology and Communication Papua; Partially, information, Computer Networks and Human Resources have a significant effect on employee performance Department of Information Technology and Communication Management in Papua province, and Human Resources is the dominant factor that greatly affects the performance of the employee Department of Information Technology and Communication Management in Papua province.